Business Incubators as a Factor for the Development of SMEs in Kosovo - Enis Mulolli; Xhavit Islami; Nagip Skenderi (International Journal of Management, Accounting and Economics, 2017)
This paper treats the role of business incubators in the increase of small and middle enterprises in Kosovo. Business incubators offer the opportunity of growth of SMEs in the start-up phase by creating a comfortable supportive environment for a certain time since their establishment. According to the literature, the business incubator is an important instrument for local, national and beyond economic development. Knowing the difficulties that start-ups face, business incubators enable start-ups to have access in: managerial assistance, mentorship, finances, Office space for the lower price than the market price, flexible rental, technical support services, common management services and secretary as well as other support services. Their opportunities are welcomed and hopeful for the initial phases of the development of SME in Kosovo. The purpose of this paper is to estimate the role of incubators and their impact on business development in Kosovo using the analytical approach. To achieve the objective of this paper, we have analyzed data from existing literature of various authors and reports for the role of business incubators. According to results derived from this paper, we came to a conclusion that business incubators are the main factor for the development of SME and consequently, overall economic growth in Kosovo.